Performance Comparison of Machine Learning Approach for Dynamic System Identification and Control - Rakesh Kumar Pattanaik (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Mostly the industrial control for dynamic system is the challenge in recent research. The problem is too complex due to non-linear and dynamic nature. To tackle this problem popular model is chosen as Functional link Artificial Neural Network (FLANN). However, the training is performed with kernel based least mean square (K-LMS) algorithm. Further three different kernels are experienced for the proposed model. Finally, the mixed kernel is proposed for LMS based training to the FLANN model. It is capable of performing at a higher level for faster convergence while maintaining its robust characteristics. However, because of its useful function approximation properties, it has been selected as an alternate method for identifying nonlinear systems. The proposed ANNs model has been demonstrated to be applicable to the modelling of complicated dynamical systems. A comparison is made among different kernel approached as well as with the earlier methods. The results of various strategies, such as Sliding Mode, RBFN, and k-LMS-based FLANN, have been compared in a performance analysis.